Adult-onset Still's disease: an Italian multicentre retrospective observational study of manifestations and treatments in 245 patients. Issue 7 (July 2016) - Sfriso, Paolo; Priori, Roberta; Valesini, Guido; Rossi, Silvia; Montecucco, Carlo; D'Ascanio, Anna; Carli, Linda; Bombardieri, Stefano; LaSelva, Gaetana; Iannone, Florenzo; Lapadula, Giovanni; Alivernini, Stefano; et al.
Abstract Adult-onset Still's disease (AOSD) is a systemic inflammatory condition of unknown aetiology characterized by typical episodes of spiking fever, evanescent rash, arthralgia, leukocytosis and hyperferritinemia. Given the lack of data in Italian series, we promote a multicentric data collection to characterize the clinical phenotype of Italian patients with AOSD. Data from 245 subjects diagnosed with AOSD were collected by 15 centres between March and May 2013. The diagnosis was made following Yamaguchi's criteria. Data regarding clinical manifestations, laboratory features, disease course and treatments were reported and compared with those presented in other published series of different ethnicity. The most frequent features were the following: arthritis (93 %), pyrexia (92.6 %), leukocytosis (89 %), negative ANA (90.4 %) and neutrophilia (82 %). As compared to other North American, North European, Middle Eastern and Far Eastern cohorts, Italian data show differences in clinical and laboratory findings. Regarding the treatments, in 21.9 % of cases, corticosteroids and traditional DMARDs have not been able to control the disease while biologics have been shown to be effective in 48 to 58 patients. This retrospective work summarizes the largest Italian multicentre series of AOSD patients and presents clinical and laboratory features that appear to be influenced by the ethnicity of the affected subjects.